Sex Differences in Platelet Reactivity in Patients With ST-Elevation Myocardial Infarction: A Sub-Analysis of the ON-TIME 3 Trial - Tavenier, Anne H.; Hermanides, Renicus S.; Ottervanger, Jan Paul; Belitser, Svetlana V.; Klungel, Olaf H.; Appelman, Yolande; van Leeuwen, Maarten A.H.; van 't Hof, Arnoud W.J. (Frontiers in Cardiovascular Medicine, 2021)
Background Fast and adequate platelet inhibition is one of the cornerstones in the treatment of patients with ST-elevation myocardial infarction (STEMI). The aim of this analysis is to examine sex differences in platelet inhibition in the acute treatment of STEMI patients. Methods Platelet reactivity units (PRU) and ticagrelor plasma concentrations of all patients in the ON-TIME 3 were compared according to sex. All patients were pre-treated with crushed ticagrelor, aspirin and heparin. Both univariable and multivariable analyses were performed. Results In this sub-analysis of the ON-TIME 3 trial, 195 STEMI patients, of which 58 female patients (29.7%) and 137 male patients (70.3%), were analyzed. PRU-values immediately post-PCI were not different in females (median 135 (IQR 47-228)) compared to males (160 (IQR 40-219), P=0.92). Ticagrelor plasma concentrations were higher in the females at the start of primary PCI (141 ng/mL (IQR 25-491) vs. 76 ng/mL (IQR 15-245), P=0.049) and at 6 hours post-primary PCI (495 ng/mL (IQR 283-661) vs. 321 ng/mL (IQR 196-537), P=0.001) compared to males. However, immediately post-primary PCI and at 1-hour post-primary PCI no significant differences in ticagrelor concentrations were seen between sexes. In multivariable analysis, sex was significantly associated with ticagrelor concentration (P=0.04), but not with PRU (P=0.93). Conclusion Effective platelet inhibition reached by crushed ticagrelor in STEMI patients was similar in both sexes. Females had similar or even higher ticagrelor plasma concentrations up to 6 hours post-primary PCI compared with males.